2018
DOI: 10.1038/s41598-018-23481-5
|View full text |Cite
|
Sign up to set email alerts
|

In vivo depletion of serum IgG by an affibody molecule binding the neonatal Fc receptor

Abstract: Lowering the total level of Immunoglobulin G (IgG) in circulation is a promising general treatment option for many autoimmune diseases driven by pathogenic autoantibodies. The half-life of IgG in circulation is unusually long as a consequence of its interaction with the neonatal Fc receptor (FcRn), which protects it from lysosomal degradation by cells in contact with blood. Blocking the IgG/FcRn interaction prevents FcRn-mediated rescue, which may lead to increased catabolism and a lowering of the total IgG le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…IgG antibodies are the most abundant Ig-class in the circulation, especially in the fetus through placental transfer mediated by the FcRn receptors ( 82 ). Placentally transferred IgG provide protection in the first weeks of life due to the relatively long in vivo half-life of IgG (~3 weeks) ( 83 ). Of the four IgG subclasses, IgG1 can primarily be induced by soluble protein antigens and membrane proteins, IgG2 by bacterial capsular polysaccharides, IgG3 by viral antigens (like IgG1) and induce pro-inflammatory effects, and IgG4 by repeated exposure to a non-infectious antigen ( 84 ).…”
Section: Resultsmentioning
confidence: 99%
“…IgG antibodies are the most abundant Ig-class in the circulation, especially in the fetus through placental transfer mediated by the FcRn receptors ( 82 ). Placentally transferred IgG provide protection in the first weeks of life due to the relatively long in vivo half-life of IgG (~3 weeks) ( 83 ). Of the four IgG subclasses, IgG1 can primarily be induced by soluble protein antigens and membrane proteins, IgG2 by bacterial capsular polysaccharides, IgG3 by viral antigens (like IgG1) and induce pro-inflammatory effects, and IgG4 by repeated exposure to a non-infectious antigen ( 84 ).…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation for this lack of additional efficacy could be the diminished half‐life of rituximab resulting from its administration immediately after IVIg dosing 27 . Recent data have shown that rapid FcRn blockade by affibodies reduced total circulating IgG levels by up to 40%‐70% within 5‐10 days in 2 distinct preclinical models 28,29 …”
Section: Discussionmentioning
confidence: 99%
“…79,80 Administration of immunomodulatory doses of IVIG (1-2 g/kg), often used for desensitization and treatment of AMR, can reduce endogenous total IgG concentrations due to FcRn saturation. [81][82][83][84][85] Although FcRn saturation by IVIG is likely important in accelerating the clearance of pathogenic antibodies, it could also result in the rapid clearance of therapeutic antibodies as reported previously. It is therefore critical to avoid dosing therapeutic mAbs in temporal proximity to high-dose IVIG because high-dose IVIG could diminish the therapeutic benefits.…”
Section: Fc Recep Tor Neonatal (Fcrn) Manipul Ati On S For Tre Atmementioning
confidence: 74%